Networked Bodies and Extended Corporealities: Theorizing the Relationship between the Body, Embodiment, and Contemporary New Media. - White, Michele (Feminist Studies)
This article discusses connections between bodily experiences and media technology in feminist studies. Author Susan Kozel discusses the relationship between technology and embodiment in her book "Closer: Performance, Technologies, Phenomenology" by Susan Kozel. In her book "Materializing New Media: Embodiment in Information Aesthetics," author Anna Munster discusses material engagement with media.